Hospitality in Luke's Gospel Narrative - Solibut, Elto; Thomas, Art S.; Weol, Wolter (International Journal of Education, Information Technology, and Others, 2025)
Hospitality is one of the themes echoed in Christian theology with various forms of effort. This is inseparable from the fact that the Indonesian nation is a plural nation. Plurality on the one hand is a beauty, but on the other hand plurality also contains its own element of sensitivity. Therefore, the theme of hospitality is a reference to suppress and prevent potential conflicts in the midst of the reality of the plurality of this nation. This paper would like to present several passages of the Bible that reflect hospitality based on the narrative of the Gospel of Luke The reason researchers chose Luke's Gospel is because of its universal nature; touch all aspects in a plural context. The research method used is a literature study research approach. From the results of this study, it was found that hospitality has socioreligious values that include mutual respect, courtesy, acceptance, help, and a sense of solidarity, which can be widely implemented. Thus, as a Christian the implications of his faith make hospitality has no fixed place, but rather a plural reality.